Crack growth diagnostic of ball bearing using vibration analysis - Belaid, Siham; Lecheb, S.; Chellil, Ahmed; Mechakra, Hamza; Safi, Brahim; Kebir, Hocine (Zielona Góra: Uniwersytet Zielonogórski)
It is known that supported ball bearings have great effects on the vibrations of the gear transmission system, above in all the presence of local faults as well as the crack growths. For this purpose, this paper focuses on shock and vibration crack growth diagnostic of ball bearing using vibration analysis.
Keywords: ball bearing; vibration analysis; frequency; cracking; diagnosis; fatigue life